Nikon d3200 digital field guide. - Thomas, J. Dennis (Digital field guide., 2012)
A colorful, portable guide to all the features of Nikon's D3200 dSLRThe Nikon D3200 dSLR camera is packed with fabulous features like a 24-megapixel sensor, full HD video capability with fulltime autofocus, and 4 frames-per-second continuous shooting mode. This full-color guide provides instructions for all the buttons, dials, modes, and menus plus a refresher course in photography basics. It illustrates the essentials of lighting, composition, and exposure with plenty of examples, and author Alan Hess, veteran concert photographer, even includes professional tips on improving portraits, candi.